The past and future of the European Social Model - Christoph Hermann; Birgit Mahnkopf (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2010)
This paper should be understood as a modest contribution to an emerging debate about the conclusions from the crisis and the future of the European Social Model. Inspired by the writings of Karl Polanyi, the first section of the paper discusses the nature and some of the main characteristics of the European Social Model. In the second part we summarise major changes that have been introduced in the last three decades and which amount to an erosion of the ESM. Special attention in this process is paid to the role of the European Union. The third part of the paper then discusses a possible revitalisation of the ESM based on three major projects: the renewal of the European welfare states, the reconstruction and expansion of the public sector and the democratisation of the EU and of European societies.
Keywords: 330